Dervish Mehmed bin Mubarek Geray Genghisi. The Chronicle “Tarikh-i Mehmed Geray” (“Mehmed Geray’s History”). Part 1 - Refat Abduzhemilev (Крымское историческое обозрение)
The Chronicle “Tarikh-I Mehmed Geray” (1682–1703) by Crimean Tatar historiographer Dervish Mehmed bin Mubarak Geray Ginghisi is the narrative source reflecting the history of the Ottoman state in 1682–1703. The date of the work is 1703 (completed in the month of Rejeb 1115). A copy of the chronicle has been preserved in the funds of the Austrian National Library (Österreichische Nationalbibliothek) under the cipher (inventory number). No. 1080, Cod. H.O.86 HAN MAG. Volume (folio) – 125 sheets in taalik script, sheets are small. There are verses on 125 sheets. The manuscript is not marked with the title, but has an appraisal prescript: “Tarih-i Mehmed Geray: Qara Mustafa Paşa cenklerin söyler Avcı Sultan Mehmed Han vaqtlarından Sultan Ahmed Han, biñ yüz on beş tarihınacek söyler bir maqbul tarihdır” / “Tarikh-i Mehmed Geray: the generally accepted history in the narration about the wars of Kara Mustafa Pasha, since the times of Avjy (“The Hunter”) Sultan Mehmed Khan till Sultan Ahmed Khan, up to the year one thousand one hundred and fifteen”.